Adjuvant chemotherapy for rectal cancer: Current evidence and recommendations for clinical practice. (February 2020) - Bregni, G.; Akin Telli, T.; Camera, S.; Deleporte, A.; Moretti, L.; Bali, A.M.; Liberale, G.; Holbrechts, S.; Hendlisz, A.; Sclafani, F.
Highlights: The mainstay of treatment for locally advanced rectal cancer is (chemo) radiotherapy and surgery. Trials have not given clear indications on the added value of adjuvant chemotherapy. A risk-adapted algorithm should be considered in clinical practice. Pros and cons of adjuvant chemotherapy should be discussed with ypStage II and III patients. Patients should be informed of the evidence gap and be empowered in the decision making. Abstract: While adjuvant chemotherapy is an established treatment for pathological stage II and especially stage III colon cancer, its role in the multimodal management of rectal cancer remains controversial. As a result, there is substantial variation in the use of this treatment in clinical practice. Even among centres and physicians who consider adjuvant chemotherapy as a standard treatment, notable heterogeneity exists with regard to patient selection criteria and chemotherapy regimens. The controversy around this topic is confirmed by the lack of full consensus among national and international clinical guidelines. While most of the clinical trials do not support the contention that adjuvant chemotherapy may improve survival outcomes if pre-operative (chemo)radiotherapy is also given, these suffer from many limitations that preclude drawing definitive conclusions. Nevertheless, in the era of evidence-based medicine, physicians should be guided by the available data and refrain from extrapolating results of adjuvant colon cancer trials to inform treatment decisions for rectal cancer. Patients should be informed of the evidence gap, be given the opportunity to carefully discuss pros and cons of all the possible management options and be empowered in the decision making. In this article we review the available evidence on adjuvant chemotherapy for rectal cancer and propose a risk-adapted decisional algorithm that largely relies on informed patient preferences.